ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN DI SHOESHOLIC SHOP TUNJUNGAN PLAZA SURABAYA - Stefandy Pribudi (Agora, 2018)
This research aims to determine what factors can influence purchasing decision at Shoesholic Shop Tunjungan Plaza Surabaya and also what is the most influencing factor on consumer purchasing decision. These factors can be used as a basis of business strategy and marketing strategy in order to increase profits for Shoesholic Shop’s owner.This research is a quantitative research where consumers who have bought shoes products at Shoesholic Shop Tunjungan Plaza Surabaya used as the population. As much as 100 samples have been taken using purposive sampling technique from unspecified number of population.Questionnaires were distributed at the Shoesholic Shop Tunjungan Plaza Surabaya as a process of collecting data which was then processed using Confirmatory Factor Analysis (SPSS).The results showed that there are four factors influencing purchasing decision at Shoesholic Shop Tunjungan Plaza Surabaya, these are: psychological factors, marketing mix factors, social factors, and situational factors. The most dominant factor in influencing consumer purchase decision in Shoesholic Shop Tunjungan Plaza Surabaya is social factor.